Characterization of tetraethylene glycol-based deep eutectic solvents and their potential application for dissolving unsaturated fatty acids - Hayyan, Adeeb; Hadj-Kali, Mohamed Kamel Omar; M. Salleh, M. Zulhaziman; Hashim, Mohd Ali; Rubaidi, Siti Rohayu; Hayyan, Maan; Zulkifli, M.Y.; Rashid, Shahidah Nusailah; Mirghani, Mohamed Elwathig Saeed; Ali, Emad; Basirun, Wan Jefrey (Elsevier, 2020)
Deep eutectic solvents (DESs) are credible alternatives for ionic liquids. Most DESs have favourable properties such as lower production cost, biodegradability and are environmental friendly. In this work, tetraethylene glycol (TTEG)-based DESs were successfully prepared by mixing TTEG and choline chloride at different molar ratios. The physicochemical properties such as conductivity, freezing point, density, surface tension and viscosity were measured at temperatures between 298.15 K and 353.15 K. It was found that the molar ratio of both compounds affected the physicochemical properties. As the solubility of unsaturated fatty acids, such as oleic acid and linoleic acid, in these DESs are industrially significant, this property became an important consideration. Computer simulations using the COSMO-RS program which is based on the interpretation of the σ-profiles, as well as the evaluation of Gibbs energy change of mixing were in excellent agreement with the experimental results. To the best of our knowledge, this is the first report on TTEG-based DESs which were used to dissolve unsaturated fatty acids. This work could introduce a new perspective in lipids chemistry, biofuel production, food processing and vegetable oil extraction.